Cr2Te3 thin films for integration in magnetic topological insulator heterostructures - Burn, DM; Duffy, L; Fujita, R; Zhang, S; Figueroa, AI; Herrero-Martin, J; Van Der Laan, G; Hesjedal, T (Nature, 2019)
Chromium telluride compounds are promising ferromagnets for proximity coupling to magnetic topological insulators (MTIs) of the Cr-doped (Bi,Sb)2(Se,Te)3 class of materials as they share the same elements, thus simplifying thin film growth, as well as due to their compatible crystal structure. Recently, it has been demonstrated that high quality (001)-oriented Cr2Te3 thin films with perpendicular magnetic anisotropy can be grown on c-plane sapphire substrate. Here, we present a magnetic, and soft xray absorption spectroscopy study of the chemical and magnetic properties of Cr2Te3 thin films. X-ray magnetic circular dichroism (XMCD) measured at the Cr L2,3 edges gives information about the local electronic and magnetic structure of the Cr ions. We further demonstrate the overgrowth of Cr2Te3(001) thin films by high-quality Crdoped Sb2Te3 films. The magnetic properties of the layers have been characterized and our results provide a starting point for refining the physical models of the complex magnetic ordering in Cr2Te3 thin films, and their integration into advanced MTI heterostructures for quantum device applications.